Mechanical Properties of High Volume Fly Ash Concrete Reinforced with Hybrid Fibers - Rooban Chakravarthy; Srikanth Venkatesan; Indubhushan Patnaikuni (Advances in Materials Science and Engineering)
Fly ash substitution to cement is a well-recognized approach to reduce CO2 emissions. Although fly ash concrete is prone to brittle behavior, researchers have shown that addition of fibers could reduce brittle behavior. Previous research efforts seem to have utlised a single type of fiber or two types of fibers. In this research, three types of fibers, steel, polypropylene, and basalt as 0%, 0.50%, 0.75%, and 1% by volume of concrete, were mixed in varying proportions with concrete specimens substituted with 50% fly ash (class F). All specimens were tested for compressive strength, indirect tensile strength, and flexural strength over a period of 3 to 56 days of curing. Test results showed that significant improvement in mechanical properties could be obtained by a particular hybrid fiber reinforcement combination (1% steel fiber, 0.75% polypropylene fiber, and 0.75% basalt fiber). The strength values were observed to exceed previous research results. Workability of concrete was affected when the fiber combination exceeded 3%. Thus a limiting value for adding fibers and the combination to achieve maximum strengths have been identified in this research.